Approximate execution and grouping of critical sections for performance-accuracy tradeoff - ALTUNTAŞ, ZUHAL; ARSLAN YILMAZ, SANEM; BOZ, BETÜL (My University, 2023)
© 2023 John Wiley & Sons, Ltd.Approximate computing enhances the performance and energy efficiency of applications, while still achieving acceptable accuracy. Some of the multithreaded applications can tolerate the accuracy loss when critical sections are approximately executed, which in turn will eliminate the synchronization overhead of these applications and increase their performance. In this study, our objective is to explore the behavior of the critical sections and selectively skip the ones yielding performance improvements with an acceptable accuracy loss. We have observed the behavior of 62 critical sections of 4 selected applications. We have grouped them depending on their effects on program execution and skipped or approximated them accordingly. Our experimental study indicates that skipping 76% of the critical sections offers 2.5 (Formula presented.) performance gain with 16% accuracy loss for Raytrace whereas 1.4 (Formula presented.) performance improvement with 17% accuracy loss is obtained for Radiosity on average when 36% of the critical sections are skipped. For Water_NSquared the performance gain is 1.1 (Formula presented.) with 9% accuracy loss on average with 79% of critical sections skipped. For the Ocean_CP application we see a performance improvement of 1.6 (Formula presented.) with accuracy loss 1% when we skip 38% of critical sections.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Bilgisayar Bilimleri; Biyoenformatik; Veritabanı ve Veri Yapıları; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Computer Sciences; bioinformatics; Database and Data Structures; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, TEORİ VE YÖNTEM; BİLGİSAYAR BİLİMİ, YAZILIM MÜHENDİSLİĞİ; TELEKOMÜNİKASYON; MATEMATİK, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; COMPUTER SCIENCE, THEORY & METHODS; COMPUTER SCIENCE, SOFTWARE ENGINEERING; TELECOMMUNICATIONS; MATHEMATICS, APPLIED; Teorik Bilgisayar Bilimi; Fizik Bilimleri; Yazılım; Bilgisayar Bilimi Uygulamaları; Bilgisayar Ağları ve İletişim; Hesaplamalı Teori ve Matematik; Theoretical Computer Science; Physical Sciences; Software; Computer Science Applications; Computer Networks and Communications; Computational Theory and Mathematics; accuracy; approximate computing; critical section; parallel application; performance